Long-term trends in fish length-at-age, catch-at-length and condition of the Namibian and South African commercially exploited species - Iyambo, Elago Martha (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Fish growth rate is a flexible trait that can evolve in response to fishing or environmental change. Therefore, knowledge of fish growth rate patterns, long-term and short-term responses to fishing effort and environmental change is important for fisheries management in the Benguela. Historical and current age length keys have been used as indicators of annual fish growth in the Benguela, the growth rate study on Merluccius paradoxus demonstrated long-term changes in growth over three decades as a response to fishing. However, the fish growth rate patterns, in relation to fishing effort and environmental change patterns are still not known for the many commercially important stocks in the Benguela. The specific objectives of the project were to determine the annual variability and long-term trends, in annual mean lengths-at-age, catch-at-length and fish condition of 17 commercially exploited resources, targeted and bycatch in Namibia and South Africa in relation to environmental changes (sea surface temperature). The results showed that there was a significant decrease in mean length at age 7 for Merluccius capensis (Namibian stock), a significant decrease in mean length at ages 3 to 7 for South African M. capensis and a significant increase in mean length at ages 2 to 6 for South African M. paradoxus Fishery-induced evolution may be the reason for the increase in mean length in the early stages of hake. A regime shift was detected in the mean length at age 1 for Etrumeus whiteheadi (South African stock) caused by changes in water temperatures. A decrease in mean length of the catch was observed for Namibian M. capensis and the reason for this could have been the stock being overexploited during the years of the observed trend (1968 to 1987). Historically both the Namibian Lophius vomerinus and Helicolenus dactylopterus were bycatch of the hake fishery, therefore, the decrease in their mean length of the catch may be due to increased bycatch mortalities due to increased hake catches. The improvement in the management measures of the Jasus lalandii fishery and possible favourable oxygen fluctuation might have caused the stock to increase in mean length of the catch between 1977 and 1982. Fish condition showed a significant difference in stocks between years. Fish condition of M. capensis, M. paradoxus and T. capensis were analysed. The rest of the commercial stocks were omitted because there was limited length-weight data. For Namibian M. capensis the spawning season may have caused fish to have the best condition in 1987 and while higher temperatures in 1983 may have led to the worst condition in 1983. Higher prey availability in 1979 for Namibian M. paradoxus could have been the reason for fish with best condition being found in 1979. T. capensis had the highest condition index in 1986 when cooler summer SST prevailed that may have been more favourable for T. capensis to live in. July, September and January SSTs were significantly negatively correlated with the mean length of M. capensis at age 3. This was perhaps due to upwelling intensity and plankton productivity which increases in winter and decreases in summer. A separate study of the impacts of fishery-induced changes and density-dependence on fish growth rate, as well as the effects of other environmental variables is recommended. Since data for some species was outdated, it is suggested to update biological variables and assessment for future work. This study can be used to understand the key life history characteristics of Namibian and South African exploited resources, targeted and bycatch.
Keywords: Fishery management -- South Africa; Fishery management-- Namibia; Fishes Growth; Fisheries Fishing effort; Climatic changes; Fishes Climatic factors